PENGARUH PENGENDALIAN INTERNAL BUDAYA ETIS ORGANISASI DAN KOMPENSASI TERHADAP ACCOUNTING FRAUD TENDENCY PADA PEMERINTAHAN DESA DI KOTA AMBON - W. Silooy, Revi; Atarwaman, Rita J. D.; Leiwakabessy, Theophilia F. F.; Usmany, Alfrin E. M.; N. Soepriadi, Dewi (ITB AAS Indonesia Surakarta, 2024)
that the forger obtains profit. In the public realm, accounting fraud tendency can be detected by fraud in the State Budget. Furthermore, in the period 2015-2022, 851 cases of village fund corruption were recorded which were obtained from the village budget with various modes of corruption including budget misuse practices, embezzlement of fictitious reports, budget inflation and misuse of social assistance funds for personal gain. This study aims to test and provide empirical evidence of the influence of internal control, organizational ethical culture and compensation on accounting fraud tendency. Data were obtained by distributing questionnaires to village officials with certain criteria. This study uses a quantitative approach, with multiple regression analysis techniques through the SPSS program. The results of the study show that the variables of internal control, organizational ethical culture, and compensation have a negative effect on accounting fraud tendency. Keywords : Accounting Fraud Tendency, Internal Control, Organizational Ethical Cunlture, and Compensation